Comparison between minimally invasive and open living donor hepatectomy: A systematic review and meta‐analysis. Issue 6 (June 2015) - Berardi, Giammauro; Tomassini, Federico; Troisi, Roberto Ivan
Abstract : Living donor liver transplantation is a valid alternative to deceased donor liver transplantation, and its safety and feasibility have been well determined. Minimally invasive living donor hepatectomy (MILDH) has taken some time to be accepted because of inherent technical difficulties and the highly demanding surgical skills needed to perform the procedure, and its role is still being debated. Because of the lack of data, a systematic review and meta‐analysis comparing MILDH and open living donor hepatectomy (OLDH) was performed. A systematic literature search was performed with PubMed, Embase, Scopus, and Cochrane Library Central. Treatment outcomes, including blood loss, operative time, hospital stay, analgesia use, donor‐recipient morbidity and mortality, and donor procedure costs, were analyzed. There were 573 articles, and a total of 11, dated between 2006 and 2014, fulfilled the selection criteria and were, therefore, included. These 11 studies included a total of 608 adult patients. Blood loss [mean difference (MD) = –46.35; 95% confidence interval (CI) = –94.04‐1.34; P = 0.06] and operative times [MD = 19.65; 95% CI = –4.28‐43.57; P = 0.11] were comparable between the groups, whereas hospital stays (MD = –1.56; 95% CI = –2.63 to −0.49; P = 0.004), analgesia use (MD = –0.54; 95% CI = –1.04 to −0.03; P = 0.04), donor morbidity rates [odds ratio (OR) = 0.62; 95% CI = 0.40‐0.98; P = 0.04], and wound‐related complications (OR = 0.41; 95% CI = 0.17‐0.97; P = 0.04) were significantly reduced in MILDH. MILDH for right liver procurement was associated with a significantly reduced hospital stay (OR = –0.92; 95% CI = 0.17‐0.97; P = 0.04). In conclusion, MILDH is associated with intraoperative results that are comparable to results for OLDH and with surgical outcomes that are no worse than those for the open procedure. Liver Transpl 21:738‐752, 2015 . © 2015 AASLD.